Emergency Cholecystectomy Versus Percutaneous Cholecystostomy for The Treatment of Acute Cholecystitis in High-Risk Surgical Patients - Akhtar, Naveed; Farooq, Muhammad Omar; Ilyas, Sohail; Farani, Tariq Mukhtar; Siyar, Falak (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the outcomes of emergency cholecystectomy versus percutaneous cholecystostomy for treatment of acute cholecystitis in high-risk surgical patients.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Surgery, Combined Military Hospital Quetta, Pakistan from Apr 2022 to Sep 2023.Methodology: After taking written informed consent, eighty-eight patients who fulfilled the inclusion criteria were enrolled in the study. The patients were divided into two groups of 44 each by odd and even number. Patients in Group-A underwent percutaneous cholecystostomy and in Group-B emergency cholecystectomy was performed. The outcome measures were assessed till the patients were discharged and then on the 30th postoperative day.Results: The mean age of the patients was 51.0±7.41 years in Group-A and 53.00±8.53 years in Group-B. In-hospital mortality occurred in 6(13.6%) patients in Group-A compared to 1(2.3%) patient in Group-B (p=0.049). Thirty days mortality occurred in 7(15.9%) patients in Group-A and 1(2.3%) patient in Group-B (p=0.026). Complications occurred in 4(9.1%) patients in Group-A compared to 14(31.8%) patients in Group-B (p=0.008).Conclusion: In high-risk surgical patients with acute cholecystitis, emergency cholecystectomy was significantly associated with lower rates of in-hospital and 30 days’ mortality, but higher rates of complications compared to percutaneous cholecystostomy.